PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA GENIAL.LY (ULAR TANGGA) DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK - Intan Ristri Alkhila; Raden Roro Suci Nurdianti; Kurniawan Kurniawan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The main problem in this research concerns the low learning outcomes of students in economics subjects. The aim of the research is to determine the increase in learning outcomes before and after treatment, as well as to compare the differences in the increase in learning outcomes between the experimental class which uses the Teams Games Tournament (TGT) type cooperative learning model with Genial.ly media with the snakes and ladders game and the control class which applies the learning model conventional. The research was carried out at SMA Negeri 1 Cineam using a quasi-experimental method. The research population included students in class XI IPS at SMA Negeri 1 Cineam, with a total of 62 students selected through a purposive sampling technique. The research instrument is a multiple choice test on economics subjects with 30 questions. Data analysis was carried out using the SPSS 25 program with paired sample t-test and independent sample t-test, using a significance level of 5% (0.05). The analysis results show the Sig. (2-tailed) of 0.000, which indicates a significant difference in improving learning outcomes. The experimental class that used the Teams Games Tournament (TGT) type cooperative learning model using Genial.ly media with the snakes and ladders game showed better learning results than the control class that used conventional learning methods after the treatment was given.